Evaluation of Maritime Tourism Development in Muna Regency in Southeast Sulawesi - Laode Kadar; Juhasdi Susono; Abdul Rahim (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
Broadly speaking, this study aims to obtain the results of a study regarding the evaluation of the development of marine tourism in Muna Regency in Southeast Sulawesi. The unit of analysis in this study is the Office of Tourism and Culture as one of the government agencies in Muna Regency, which is demanded to manage and contribute to the maximum revenue contribution to the Regional Original Revenue (PAD) with selected respondents and key informants are the Head of Service, Head of Division and Head of Planning and Financial Subdivision. In this study the research method used is descriptive qualitative method. The analysis tool used is the Realistic Evaluation Method with the Context-Mechanism-Outcome configuration approach. The results showed that, evaluation of the development of marine tourism in Muna Regency through the analysis of Context and Mechanism evaluation can be obtained Outcome